2019
DOI: 10.1021/jacs.9b03217
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Frustrated Lewis Pairs of CeO2 Activate CO2 for Selective Tandem Transformation of Olefins and CO2 into Cyclic Carbonates

Abstract: Effective activation of CO2 is a prerequisite for efficient utilization of CO2 in organic synthesis. Precisely controlling the interfacial events of solids shows potential for activation. Herein, defect-enriched CeO2 with constructed interfacial frustrated Lewis pairs (FLPs, two adjacent Ce3+···O2–) effectively activates CO2 via the interactions between C/Lewis basic lattice O2– and the two O atoms in CO2/two adjacent Lewis acidic Ce3+ ions. Selective cyclic carbonate production from a catalytically tandem pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(133 citation statements)
references
References 40 publications
1
132
0
Order By: Relevance
“…44-1246: Bi; JCPDS No. 34-0394: CeO 2 ), respectively [ 6 , 23 , 24 ]. The results indicated that the BiOCl was converted into metallic Bi, and the CeO 2 was apparently unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…44-1246: Bi; JCPDS No. 34-0394: CeO 2 ), respectively [ 6 , 23 , 24 ]. The results indicated that the BiOCl was converted into metallic Bi, and the CeO 2 was apparently unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 However, many challenges still remain before achieving high efficiency conversion due to the inert nature of CO2. 5 Furthermore, the hydrogen evolution reaction (HER) is kinetically more favorable and therefore competes with eCO2RR in aqueous media. 6,7 To overcome these problems, electrocatalysts with high selectivity and efficiency are highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…The huge energy consumption of the separating process restrains the development of homogenous catalysts in industry. In consequence, heterogeneous catalysts for the CO 2 cycloaddition reaction are receiving more attentions gradually in recent years, which include metal organic frameworks (MOFs), [29][30][31] covalent organic frameworks (COFs), [32][33] Ndoped porous carbon materials, [34][35] polymers, [36] layered double hydroxides (LDH), [37] defective metal oxides, [38] ionexchange resins, [39] poly(ionic liquids) (PILs) [40][41][42] and supported ionic liquids (SILs). [43] Traditional heterogeneous catalysts can be separated from products facilely, but the catalytic efficiency is relatively low.…”
Section: Introductionmentioning
confidence: 99%